Genomic Resources for Goniozus legneri, Aleochara bilineata and Paykullia maculata, Representing Three Independent Origins of the Parasitoid Lifestyle in Insects. Issue 4 (1st April 2019) - Kraaijeveld, Ken; Neleman, Peter; Mariën, Janine; de Meijer, Emile; Ellers, Jacintha
Abstract: Parasitoid insects are important model systems for a multitude of biological research topics and widely used as biological control agents against insect pests. While the parasitoid lifestyle has evolved numerous times in different insect groups, research has focused almost exclusively on Hymenoptera from the Parasitica clade. The genomes of several members of this group have been sequenced, but no genomic resources are available from any of the other, independent evolutionary origins of the parasitoid lifestyle. Our aim here was to develop genomic resources for three parasitoid insects outside the Parasitica. We present draft genome assemblies for Goniozus legneri, a parasitoid Hymenopteran more closely related to the non-parasitoid wasps and bees than to the Parasitica wasps, the Coleopteran parasitoid Aleochara bilineata and the Dipteran parasitoid Paykullia maculata . The genome assemblies are fragmented, but complete in terms of gene content. We also provide preliminary structural annotations. We anticipate that these genomic resources will be valuable for testing the generality of findings obtained from Parasitica wasps in future comparative studies.